2015
DOI: 10.14419/ijbas.v4i2.4370
|View full text |Cite
|
Sign up to set email alerts
|

Exposure of gasoline professionals to leaded gasoline in Asyut governorate

Abstract: Background: Gasoline is a complex manufactured mixture that does not exist naturally in the environment and produced from petroleum in the refining process. Gasoline discussed in this profile is automotive gasoline used as a fuel for engines in automobiles and other vehicles. Unleaded gasoline was introduced in the greater area Asyut, and 10% of the total sales of gasoline were unleaded. There were no previous studies on pollution caused by gasoline exposure in Asyut governorate in Upper Egypt, so, in this stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 17 publications
1
1
0
Order By: Relevance
“…That is why we studied the changes of NO levels in tumor target cells after treatment using Azol at a dose level of 10 and 15 mg/kg in EAC-bearing mice. It was reported that EAC inoculation induced significant increase in the serum NO and MDA levels compared to that of the normal control group [50]. In the present study administration of Azol at a dose level of 10 mg/ kg produced significant depletion of NO level compared to that of EAC control group, while at dose and 15 mg/kg exhibited a highly significant decreased level of NO.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…That is why we studied the changes of NO levels in tumor target cells after treatment using Azol at a dose level of 10 and 15 mg/kg in EAC-bearing mice. It was reported that EAC inoculation induced significant increase in the serum NO and MDA levels compared to that of the normal control group [50]. In the present study administration of Azol at a dose level of 10 mg/ kg produced significant depletion of NO level compared to that of EAC control group, while at dose and 15 mg/kg exhibited a highly significant decreased level of NO.…”
Section: Discussionsupporting
confidence: 51%
“…NO is produced from the amino acid L-Arginin in a reaction catalyzed by enzymes NOS., NO is a free radical having a short half-life and can react with superoxide anion O2−• producing peroxynitrite (ONOO-) anion, which can decompose to generate a strong oxidant such as the hydroxyl radical and can also induce sulphydryl oxidation and lipid peroxidation [49]. Peroxynitrite is cytotoxic and much more reactive than NO and O2−• and causing different chemical reactions in biological system including nitration of tyrosine residues of proteins producing lipid peroxidation, which inhibits the mitochondrial electron transport, and oxidation of biological thiol compounds [50,51]. NO may play a dual role in tumor progression, as it can act as promoter or antitumor promoter, depending upon its concentration as reported by Eijan et al, [52].…”
Section: Discussionmentioning
confidence: 99%